2021
DOI: 10.3390/ijms22031427
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Expression of TBP-2 in Response to Histone Deacetylase Inhibitor Treatment in Human Endometrial Cells

Abstract: Histone deacetylase inhibitors (HDACi) induce apoptosis preferentially in cancer cells by caspase pathway activation and reactive oxygen species (ROS) accumulation. Suberoylanilide hydroxamic acid (SAHA), a HDACi, increases apoptosis via altering intracellular oxidative stress through thioredoxin (TRX) and TRX binding protein-2 (TBP-2). Because ROS accumulation, as well as the redox status determined by TBP-2 and TRX, are suggested as possible mechanisms for endometriosis, we queried whether SAHA induces apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…These findings suggest a correlation between POLR2J and UPR in GBM, where POLR2J knockdown enhances UPR activation. Given that HDAC inhibitors induce apoptosis in cancer cells through ROS accumulation [39], POLR2J silencing could potentially enhance the anti-cancer activity of vorinostat by increasing ROS accumulation, presenting a novel chemo-sensitization strategy for vorinostat treatment in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest a correlation between POLR2J and UPR in GBM, where POLR2J knockdown enhances UPR activation. Given that HDAC inhibitors induce apoptosis in cancer cells through ROS accumulation [39], POLR2J silencing could potentially enhance the anti-cancer activity of vorinostat by increasing ROS accumulation, presenting a novel chemo-sensitization strategy for vorinostat treatment in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicated that POLR2J was correlated with oxidoreductase activity and UPR in GBM, and POLR2J knockdown enhanced ROS-UPR in GBM cells. HDAC inhibitors induce apoptosis in cancer cells by ROS accumulation [39]. Thus, POLR2J silence might enhance the anti-cancer activity of vorinostat by increasing ROS accumulation, and POLR2J silence might be a novel chemosensitization strategy for vorinostat treatment against GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al treated eutopic and ectopic human endometrial stromal cells with suberoylanilide hydroxamic acid and concluded that the aforementioned HDACI significantly upregulated the Thioredoxin (TRX) Binding Protein-2 (TBP-2) mRNA and protein expression, led to the reduction of the TRX/TBP-2 ratio, induced apoptosis, and halted the transfection of short-interfering TRX [55]. Moreover, Zheng et al first induced endometriosis in Krüppel-like factor 11 (Klf11) -/-mice through surgical autologous uterine tissue implantation and treated them with suberoylanilide hydroxamic acid, but did not observe any changes in collagen 1A1 expression and, consequently, the extent of fibrosis.…”
Section: Suberoylanilide Hydroxamic Acidmentioning
confidence: 99%